Thymoma with immunodeficiency with multiple recurrent oral herpetic infections - Yavuz Sinan Aydintug; Gurkan Rasit Bayar; Aydin Ozkan; Omer Gunhan; Ugur Musabak (Elsevier, 2016)
Thymomas with immunodeficiency (formerly Good's syndrome) are a rare acquired disease of combined T- and B-cell immunodeficiency accompanying a thymoma. Recurrent opportunistic infections associated with disorders of both humoral and cell-mediated immunity frequently accompany this rare primary, adult-onset immunodeficiency. This is a report of a case of a thymoma with immunodeficiency in a 65-year-old male patient who developed recurrent oral herpetic infections. He consulted us about recurrent vesiculo-ulcerative lesions on his tongue, lower lip, and buccal mucosa. Results of laboratory examinations indicated hypogammaglobulinemia accompanied by diminished B cells in the peripheral blood, which is consistent with the characteristic features of a thymoma with immunodeficiency. After a diagnosis confirming herpes simplex virus infection, systemic antiviral therapy was administered, which was effective for his vesiculo-ulcerative lesions at follow-up. When an intractable infection accompanied by a thymoma is encountered, increased awareness about the clinical and immunological profiles of this primary immunodeficiency may help in its early diagnosis, thereby preventing mortality.